Elevated levels of hair cortisol concentrations in professional dementia caregivers. (2nd November 2021) - Rippon, Daniel; McDonnell, Andrew; Bristow, Matt; Smith, Michael A.; McCreadie, Michael; Wetherell, Mark A.
Abstract: Providing care for people with dementia can be a highly stressful profession. Hair Cortisol Concentration (HCC) levels have been used as a biological marker for HPA axis activity to demonstrate that informal caregivers of people with dementia could be vulnerable to chronic stress. The current study aimed to progress the findings of research conducted with informal caregivers and is the first study to assess HCC as a biological indicator of stress in professional carers of people with dementia. HCC levels were compared between 32 professional dementia caregivers (30 females with a mean age of 45.83 and 2 males with a mean age of 24.50), 45 employees working in higher education settings (42 females with a mean age of 38.66 and 3 males with a mean age of 31.89) and 88 undergraduate students (67 females with a mean age of 24.04 and 21 males with a mean age of 23.91). Analysis of HCC was used to assess HPA axis activity over 1 month. A one-way ANCOVA, with age and gender being included as covariates, revealed that higher levels of HCC were observed in professional dementia carers than people who worked within higher education settings and undergraduate students. The results indicated that professional dementia caregivers may experience stress to the extent of activating biological stress responses at a greater frequency in comparison to people who work in higher education and undergraduate students. However, no significant differences were observed in the perceived stress levels reported across dementia caregivers, professionals working in higher education, and undergraduate students. These findings highlight the requirement to ascertain the extent to which work-related tasks or other factors, specific to the profession of caring for people with dementia, could elicit heightened HPA stress reactivity.